Experimental investigation of mechanical sustainability and acoustic performance of fly ash cenosphere/epoxy polymer composites - Sriharsha Hegde; N.H. Padmaraj; V. Siddesh; T.S. Sunaya; K. Adithya Kini; Vishal K. Sanil (Journal of King Saud University: Engineering Sciences)
Hollow spherical fly ash cenosphere is a by-product of the coal firing process in thermal power plants and nowadays has become a substitute for the other organic fillers in the composite industry. The present study investigates the mechanical and acoustic performance of cenosphere/epoxy-based polymer composites. Void content, Shore Hardness, Tensile, Flexural, Impact, and Acoustic studies were conducted on epoxy specimens containing 0, 3, 5, and 7% of cenosphere by weight. Surface morphology and failure pattern of the tensile failure samples were investigated using the scanning electron microscope technique. Incorporation of cenosphere into epoxy reduced the void content from 4.27 to 2.54 % and increased the Shore hardness from 80.8 ± 1.44 to 85.8 ± 1.78 when the filler content was increased from 3 to 5%. Impact strength, Tensile and Flexural modulus showed an incremental trend with the increase in the weight percentage of the cenosphere. Examination of the tensile failure surface showed the presence of twist hackles and better interlocking of cenosphere with epoxy matrix. The density of the specimens played vital role in sound absorption characteristics. The addition of the cenosphere in epoxy deteriorates the sound absorption behaviour of the material as compared to neat epoxy.